Safety and outcome of children, adolescents and young adults participating in phase I/II clinical oncology trials: a 9-year center experience - Anna Pujol Manresa; Anna Pujol Manresa; Susana Buendía López; Maitane Andión; Maitane Andión; Blanca Herrero; Blanca Herrero; Álvaro Lassaletta; Manuel Ramirez; Manuel Ramirez; David Ruano; David Ruano; et al. (Frontiers Media S.A., 2024)
IntroductionEnrolling children with cancer in early phase trials is crucial to access innovative treatments, contributing to advancing pediatric oncology research and providing tailored therapeutic options. Our objective is to analyze the impact of these trials on patient outcomes and safety, and to examine the evolution and feasibility of trials in pediatric cancer over the past decade.MethodsAll patients recruited in pediatric anticancer phase I/II clinical trials from January 2014 to December 2022 were included. Clinical records and trial protocols were analyzed.ResultsA total of 215 patients (median age 11.2 years, range 1-29.5) were included in 52 trials (258 inclusions). Patients with extracranial solid tumors (67%), central nervous system (CNS) tumors (24%), and leukemia (9%) were included. The most common investigational drugs were small molecules (28.3%) and antibodies (20.5%). Serious adverse events were experienced by 41% of patients, 4.4% discontinued treatment because of toxicity and two had toxic deaths. Median event-free survival was 3.7 months (95%CI: 2.8-4.5), longer in phase II trials than in phase I (2 vs. 6.3 months; p ≤ 0.001). Median overall survival was 12 months (95%CI: 9-15), higher in target-specific vs. non-target-specific trials (14 vs. 6 months; p ≤ 0.001).DiscussionA significant and increasing number of patients have been included in early clinical trials, suggesting that both oncologists and families consider it valuable to be referred to specialized Units to access new therapies. Moreover, our data suggests that participation in early clinical trials, although not without potential toxicities, might have a positive impact on individual outcomes.